2013
DOI: 10.1051/0004-6361/201220537
|View full text |Cite
|
Sign up to set email alerts
|

Databases and tools for nuclear astrophysics applications

Abstract: An update of a previous description of the BRUSLIB + NACRE package of nuclear data for astrophysics and of the web-based nuclear network generator NETGEN is presented. The new version of BRUSLIB contains the latest predictions of a wide variety of nuclear data based on the most recent version of the Brussels-Montreal Skyrme-Hartree-Fock-Bogoliubov model. The nuclear masses, radii, spin/parities, deformations, single-particle schemes, matter densities, nuclear level densities, E1 strength functions, fission pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 112 publications
0
126
0
Order By: Relevance
“…This MACS is compared with the data of KADoNiS [17], BRUSLIB [18] and Tonchev et al [19] as well as that calculated from TENDL-2015 in Fig. 3.…”
Section: Neutron Capture Cross Sectionsmentioning
confidence: 90%
“…This MACS is compared with the data of KADoNiS [17], BRUSLIB [18] and Tonchev et al [19] as well as that calculated from TENDL-2015 in Fig. 3.…”
Section: Neutron Capture Cross Sectionsmentioning
confidence: 90%
“…9001 Tables of nuclear level densities, E1 gamma-ray strengths, nuclear matter densities, fission paths have all been determined from the sole BSk14 interaction and are available either in the RIPL-3 [25] library, in the TALYS code [29] or the BRUSLIB nuclear data library [30]. In the latest TALYS version, however, the theoretical nuclear masses are those obtained with BSk17 [11], the first interaction providing a root mean square deviation with experimental masses lower than 600 keV.…”
Section: Cnr * 15mentioning
confidence: 99%
“…Using such ingredients has already shown interesting features which can clearly not be addressed with traditional phenomenological approaches. An example, illustrated in Figure 4, concerns the possibility offered to study continuum spin and parity distribution deviating from the statistical hypothesis with a significant impact on isomer production [30].…”
Section: Cnr * 15mentioning
confidence: 99%
“…These are important for a number of issues, including: (1) rate estimates for reactions where no experimental nuclear physics information exists; (2) estimation of stellar rates from experimental rates, and extrapolation of Experimental data are taken from the compilation of Bao et al (2000), as well as from more recent measurements compiled in Xu et al (2013). Note that for the heavier target nuclei (A 50), most experimental and theoretical values agree within a factor of two.…”
Section: Theoretical Reaction Rates: Talysmentioning
confidence: 99%
“…See, in particular, the compilation of Bao et al (2000) and references found in Xu et al (2013). For those reactions, TALYS (laboratory) Maxwellian-averaged cross sections are normalized using the experimental value at 30 keV to ensure an accurate description in the whole temperature range, the Hauser-Feshbach being known to provide a proper description of the energy dependence of the reaction cross section.…”
Section: Theoretical Reaction Rates: Talysmentioning
confidence: 99%